Wage and Technology Dispersion - Acemoglu, D.; Shimer, R. (Review of Economic Studies, 2000)
This paper explains why firms with identical opportunities may use different technologies and offer different wages. Our key assumption is that workers must engage in costly search in order to gather information about jobs (Stigler (1961)). In equilibrium, some firms adopt high fixed cost, high productivity technologies, offer high wages, and fill job openings quickly. Other firms adopt less capital-intensive technologies and offer low wages, hiring mostly uninformed workers. In equilibrium, the amount of wage dispersion leaves workers indifferent about whether to gather information, and the fraction of informed workers leaves firms indifferent about their wage and technology choice. We show that worker search, which would appear to be a rent-seeking activity in partial equilibrium, may be efficiency-enhancing in general equilibrium.